1997
DOI: 10.1002/pro.5560060625
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance assignment and secondary structure of an ankyrin‐like repeat‐bearing protein: Myotrophin

Abstract: Abstract:Multidimensional heteronuclear NMR has been applied to the structural analysis of myotrophin, a novel protein identified from spontaneously hypertensive rat hearts and hypertrophic human hearts. Myotrophin has been shown to stimulate protein synthesis in myocytes and likely plays an important role in the initiation of cardiac hypertrophy, a major cause of mortality in humans. Recent cDNA cloning revealed that myotrophin has 118 amino acids containing 2.5 contiguous ANK repeats, a motif known to be inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…NMR Spectroscopy-Untagged, full-length Myotrophin and Myotrophin-E33A cloned into the pET3a vector (6) were expressed in BL-21(DE3) pLysS cells in minimal medium containing 0.4% glucose and 0.1% 15 NH 4 Cl, as described previously (2,23). Each protein was purified from 1 liter of culture by anion exchange chromatography, using a Resource Q column (GE Healthcare) and a gradient of 0.1-1 M NaCl.…”
Section: Expression and Purification Of Recombinant Myotrophin Proteimentioning
confidence: 99%
See 1 more Smart Citation
“…NMR Spectroscopy-Untagged, full-length Myotrophin and Myotrophin-E33A cloned into the pET3a vector (6) were expressed in BL-21(DE3) pLysS cells in minimal medium containing 0.4% glucose and 0.1% 15 NH 4 Cl, as described previously (2,23). Each protein was purified from 1 liter of culture by anion exchange chromatography, using a Resource Q column (GE Healthcare) and a gradient of 0.1-1 M NaCl.…”
Section: Expression and Purification Of Recombinant Myotrophin Proteimentioning
confidence: 99%
“…To dissect the structural basis of myotrophin function, we previously determined the solution structure of myotrophin (2,23), which consists of four ANK repeats. ANK repeat motifs are often involved in protein-protein and protein-nucleic acid interactions (24,25).…”
mentioning
confidence: 99%
“…7A) (11,12) and the three-dimensional structure of I B␣ (Fig. 7B) (13, 14), where NF B-interacting domains were well characterized.…”
Section: Three-dimensional Structural Alignment Of Myo/v1 With Rel-inmentioning
confidence: 99%
“…We recently reported that Myo/V1 protein exhibits significant homology to I B␣ protein and that Myo/V1 can disrupt the NF B-DNA complexes in vitro (3). Utilizing our recombinant Myo/V1 protein, the NMR structure of Myo/V1 was determined (11,12), and the ankyrin repeats of Myo/V1 exhibited structural features similar to those of I B␣ (13,14) at the three-dimensional level.…”
mentioning
confidence: 94%
“…A solution structure of V-1 shows two full ankyrin repeat motifs in tandem, with additional incomplete repeats at the amino and carboxyl termini (11,12). An ankyrin repeat consists of a ␤ hairpin loop followed by a pair of anti-parallel ␣ helices connected by a short turn sequence (13).…”
mentioning
confidence: 99%